Comparison of Functional Capacity using Primary Percutaneous Coronary Intervention with Pharmacological Therapy on ST Elevation Acute Coronary Syndrome Patients - Wardhani, Andini Nurkusuma; Achmad, Chaerul; Sastradimaja, Sunaryo B. (Althea Medical Journal, 2015)
Background: Acute Coronary Syndrome (ACS) is a shift manifestations pattern of ischemic myocardium.Â Revascularization either with Primary Percutaneous Coronary Intervention (PCI) or pharmacologicalÂ therapy is an optional treatment for ST Elevation Acute Coronary Syndrome (STEACS) patients. The aimÂ of the study was to compare the functional capacity using six-minute walking test on STEACS patients whoÂ underwent Primary PCI or pharmacological therapy.Methods: A cross sectional study was conducted from September to October 2012 to 35 STEACS patientsÂ who were treated after two years. The samples were obtained from the list of patients at Dr. Hasan SadikinÂ General Hospital. Inclusion criteria consisted of patients diagnosed as STEACS, cooperative and notÂ experiencing cognitive disturbance. The exclusion criteria were STEACS patients with unstable angina orÂ myocardial infarct in the last month, stable exertional angina, and pregnant women. The patients underwentÂ 6 minutes walking test,VO2max was measured using theCalahin and Cooper formula, then MetabolicÂ Equation Task (METs) was calculated. Data were analyzed by unpaired T-test.Results: There were 19 Primary PCI and 16 pharmacological therapy patients. The average of age betweenÂ the two groups was distributed evenly. Most of the STEACS patients were male, had a college/academicÂ degree and were retired. Patients treated with pharmacological therapy had higher average of VO2 max andÂ METs than patients with Primary PCI. There was no significantly differences of METs between those groupsÂ (p>0.05)Conclusions: There were no significantly differences of functional capacity in STEACS patients treated withÂ Primary PCI or Pharmacological therapy. [AMJ.2015;2(1):162â6]